Modern devices for microinvasive glaucoma surgery - Yusef, Yu; Antonov, A A; Makarova, A S; Ovsepyan, S A; Mozharovskaya, M V (Vestnik oftal'mologii, 2025)
The main controllable factor in glaucoma is intraocular pressure, which is stabilized by medication, laser and surgical treatment methods. Over the past 20 years, advancements in surgical techniques for antihypertensive interventions have led to the emergence of a new class of procedures called microinvasive glaucoma surgery (MIGS). This review focuses on Russian and foreign microinvasive drainage devices that are currently the most widely used. For a large number of glaucoma patients, when traditional treatment methods are not effective and safe enough, MIGS using modern shunts is often the only way to stabilize intraocular pressure.